2007
DOI: 10.1080/00015458.2007.11680006
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Cranial Nerve Injuries During Carotid Endarterectomy

Abstract: CNI is still a significant postoperative complication of carotid endarterectomy. Despite increasing use of CEA, the incidence of CNI has decreased probably because of increased awareness of the possibility of cranial nerve damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
0
27
0
5
Order By: Relevance
“…50 A literature review calculated a 9% risk (range, 2%-27%) of temporary palsy after CEA in patients without a hostile neck. 51 Two other extensive studies reported a rate of 5.0% with only 0.5% lasting more than a few months in patients at normal risk. 52,53 Furthermore, a rate of 7.7% in a high-risk group with local risk factors was observed without a significant difference with the reference low-risk group (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…50 A literature review calculated a 9% risk (range, 2%-27%) of temporary palsy after CEA in patients without a hostile neck. 51 Two other extensive studies reported a rate of 5.0% with only 0.5% lasting more than a few months in patients at normal risk. 52,53 Furthermore, a rate of 7.7% in a high-risk group with local risk factors was observed without a significant difference with the reference low-risk group (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…This is much lower than the figures reported in the literature (up to 8%). [27] This may be due to the experience of the team performing CEA.…”
Section: Discussionmentioning
confidence: 99%
“…His aim was to disclose the incidence of CNI after surgery and changes thereof during the last 25 years. He reported that CNI is still a significant postoperative complication after CEA but with decreasing incidence despite the increasing numbers of CEA procedures [37]. Mehta et al reported an incidence of CNI of 3% in 59 patients in redo CEA procedures [36].…”
Section: Cranial Nerve Injuries (Cni)mentioning
confidence: 98%
“…Infrequently CNI may be life-threatening in cases of injury of the glossopharyngeal or bilateral recurrent laryngeal nerve. The literature reports a broad range of incidence ranging from less than 1-25% of CNI after CEA whereby the lowest rates are seen in the center with a high volume of carotid artery endarterectomies [18,[33][34][35][36][37][38][39] (Table 3). Sajid et al reviewed the literature with regard to CNI after CEA.…”
Section: Cranial Nerve Injuries (Cni)mentioning
confidence: 99%